Adsorption of Methyl Orange from Aqueous Solution using Ni/Al LDH Modified with Camellia sinensis Leaf Extracts - Amri Amri; Heroldinho Arieveali (Indonesian Journal of Material Research, 2026)
Water pollution caused by dye pollutants such as methyl orange (MO) can have a negative impact on humans, living organisms, and ecosystems. Adsorption is one of the promising methods in overcoming the presence of MO pollutants. This research focuses on the synthesis of layered double hydroxide (LDH) Ni/Al composites prepared by coprecipitation method with the addition of green tea/Camellia sinensis (CS) leaf extract as supporting material. The synthesized materials obtained were then characterized using X-ray diffraction (XRD) patterns and Fourier transform infrared spectra (FTIR). The Ni/Al and Ni/Al-CS materials were then evaluated as adsorbents to adsorb MO from aquatic solutions. The maximum capacity of MO adsorption obtained was 18.519 mg.g−1 on Ni/Al LDH and 49.261 mg.g−1 on Ni/Al-CS, respectively. The Langmuir isotherm model showed the best fit to the adsorption data on both materials, while the kinetics of the adsorption process followed a pseudo second-order (PSO) model. Thermodynamic analysis (ΔG°, ΔS°, and ΔH°) showed that the MO adsorption process on both materials was spontaneous and endothermic. The regeneration process carried out four consecutive regeneration cycles showed that Ni/Al-CS material has excellent adsorbent recycling ability, which only decreased by 10.26%. In contrast to Ni/Al LDH which experienced a significant decrease of up to 31.70% in the 4th cycle. These findings suggest that Ni/Al CS material is a promising adsorbent for MO removal applications from aquatic solutions.